Interfacial characterization of poly (vinyl alcohol) fibers embedded in a calcium phosphate cement matrix: An experimental and numerical investigation - Paknahad, Ali; Petre, Daniela G.; Leeuwenburgh, Sander C.G.; Sluys, Lambertus J. (Acta biomaterialia, 2019)
[Display omitted] Because of their chemical similarity to the mineral phase of bone and teeth, calcium phosphate cements (CPCs) are extensively investigated for applications in biomedicine. Nevertheless, their applicability in load-bearing anatomical sites is restricted by their brittleness. Reinforcement of calcium phosphate cements with polymeric fibers can overcome this mechanical limitation provided that the affinity between these fibers and the surrounding matrix is optimal. To date, the effects of the fiber-matrix affinity on the mechanical properties of fiber-reinforced calcium phosphate cements are still poorly understood. The goal of this study is therefore to investigate the interfacial properties and bond-slip response between the CPC matrix and polymeric fibers. To this end, we selected poly (vinyl alcohol) (PVA) fibers as reinforcing agents because of their high strength and stiffness and their effective reinforcement of cementitious matrices. Micromechanical pull-out experiments were combined with numerical simulations based on an dedicated constitutive interfacial law to characterize the interfacial properties of PVA fibers embedded in a CPC matrix at the single fiber pull-out level. The computational model developed herein is able to predict all three main phases of pull-out response, i.e. the elastic, debonding and frictional pull-out phases. The resulting interfacial constitutive law is validated experimentally and predicts the pull-out response of fibers with different diameters and embedded lengths. To date, the effects of the fiber-matrix affinity on the mechanical properties of fiber-reinforced calcium phosphate cements are still poorly understood. In this study, we present a novel experimental protocol to investigate the affinity between poly (vinyl alcohol) PVA fibers and the calcium phosphate cement (CPC) matrix by means of single-fiber pull out tests. We determine the critical embedded length for PVA fibers with two different diameters; and we design a numerical FE model including a distinct representation of fiber, matrix and interface with a predictive interfacial constitutive law which is capable of capturing all three main phases of single-fiber pull-out, i.e. elastic, debonding and frictional stages. The resulting interfacial constitutive law is validated experimentally and predicts the pull-out response of fibers with different diameters and embedded lengths.